A Dual‐Organic‐Transistor‐Based Tactile‐Perception System with Signal‐Processing Functionality. Issue 18 (22nd February 2017) - Zang, Yaping; Shen, Hongguang; Huang, Dazhen; Di, Chong‐An; Zhu, Daoben
Abstract : Organic‐device‐based tactile‐perception systems can open up new opportunities for the next generation of intelligent products. To meet the critical requirements of artificial perception systems, the efficient construction of organic smart elements with integrated sensing and signal processing functionalities is highly desired, but remains a challenge. This study presents a dual‐organic‐transistor‐based tactile‐perception element (DOT‐TPE) with biomimetic functionality by the construction of organic synaptic transistors with integrated sensing transistors. The unique geometry of the DOT‐TPE permits instantaneous sensing of pressure stimuli and synapse‐like processing of an electric signal in a single element. More importantly, these organic‐transistor‐based tactile‐perception elements can be built into arrays to serve as bionic tactile‐perception systems. The combined biomimetic functionality of tactile‐perception systems, together with their promising features of flexibility and large‐area fabrication, makes this work represent a step forward toward novel e‐skin devices for artificial intelligence. Abstract : By the construction of organic synaptic transistors with integrated sensing transistors, a dual‐organic‐transistor‐based tactile‐perception element with pressure sensing and synapse‐like signal‐processing functions in a single element is demonstrated. This biomimetic functionality makes this work represent a step forward toward novel e‐skin devices for artificial intelligence.